The Effect of the Economic Cycle on the Structure of Bank Provisions for Bad Loans: Case of Ecuador 2004-2016 - Mendieta-Andrade, Patricio (2018)
The present article analyzes the relationship between the evolution of the provisions for bad accounts made by the banks conforming to the Ecuadorian financial system and the change in the economic cycle, expressed as changes in the Gross Domestic Product (GDP). In the correlation analysis of a data set that covers the period 2004-2016, the effect of the normative inclusion of the countercyclical provision in the structure of this account is identified, uncovering two different scenarios; One prior to the norm, in which the countercyclical relationship between the variation of the GDP and the provisions is verified, and a second scenario, after the validity of the norm, where it is possible to appreciate a change in the relationship between the variables studied, and Being verified the significance that the growth of the portfolio acquires in the explanation of the variation of the provisions.